Effects of material properties of band‐gap‐graded Cu(In, Ga)Se2 thin films on the onset of the quantum efficiency spectra of corresponding solar cells. (18th May 2022) - Thomas, Sinju; Bertram, Tobias; Kaufmann, Christian; Kodalle, Tim; Márquez Prieto, José A.; Hempel, Hannes; Choubrac, Leo; Witte, Wolfram; Hariskos, Dimitrios; Mainz, Roland; Carron, Romain; Keller, Jan; et al.
Abstract: Polycrystalline Cu(In, Ga)Se2 (CIGSe) thin‐film solar cells exhibit gradual onset in their external quantum efficiency ( EQE ) spectra whose shape can be affected by various CIGSe material properties. Apart from influences on the charge‐carrier collection, a broadening of the EQE onset leads to enhanced radiative losses in open‐circuit voltage ( V oc ). In the present work, Gaussian broadening of parameters describing the EQE onset of thin‐film solar cells, represented by the standard deviation, 𝜎 total, was evaluated to study the impacts of the effective band‐gap energy, the electron diffusion length, and the Ga/In gradient in the CIGSe absorber. It is shown that 𝜎 total can be disentangled into contributions of these material properties, in addition to a residual component 𝜎 residual . Effectively, 𝜎 total depends only on a contribution related to the Ga/In gradient as well as on 𝜎 residual . The present work highlights the connection of this compositional gradient, the microstructure in the polycrystalline CIGSe absorber, and the luminescence emission with the residual component 𝜎 residual . It is demonstrated that a flat band‐gap with no compositional gradient in the bulk of the CIGSe absorber is essential to obtain the lowest 𝜎 total values and thus result in lower recombination losses and gains in V oc . Abstract : We investigated the effect of various material properties of Cu(In, Ga)Se2 (CIGSe) absorbers on the onsets of EQE spectra of corresponding solar cells. Compositional gradients perpendicular to the substrate in the CIGSe thin films were identified as substantial contributors to the broadening of these EQE onsets, leading to radiative V oc losses